The Influence of Service Quality, Brand Image, and Patient Experience on Patient Loyalty through Patient Satisfaction: Empirical Study From RAA Soewondo Pati Regional Hospital, Indonesia - Juwito, J.; Bisri, Muhammad Cholil (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to determine the effect of service quality, brand image, and patient experience on patient loyalty with patient satisfaction as an intervening variable at RAA Soewondo Pati Regional Hospital, Indonesia. The variables in this study are service quality, brand image, patient experience, patient satisfaction, and patient loyalty. This study uses a quantitative approach. This type of research is associative research that tests the influence between variables. The number of samples is 240 respondents from a population of patients who have been hospitalized at RAA Soewondo Pati Regional Hospital, totaling 17,026 patients. Sampling used a non-probability sampling technique with a purposive sampling technique, namely BPJS patients who regularly receive treatment at RAA Soewondo Pati Regional Hospital. Data collection used a questionnaire. Data analysis used SEM on AMOS 24 software. The results of this study are: service quality has a positive and significant effect on patient satisfaction, brand image has a positive and significant effect on patient satisfaction, patient experience has no effect on patient satisfaction, service quality has a positive and significant effect on patient loyalty, brand image has no effect on patient loyalty, patient experience has a positive and significant effect on patient loyalty, and patient satisfaction has no effect on patient loyalty.